2021
DOI: 10.1002/mcda.1744
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐criteria supply chain network design using interactive decision maps

Abstract: Growing concerns about sustainability lead decision-makers to include in the supply chain network design, environmental and social impacts as well as economic objectives, which requires a balanced multi-criteria approach. In this paper, a multiobjective mixed integer model for a regional supply chain network of a fish processing industry is developed. The model and decision-making process is analysed using approximation and visualization of Pareto frontier in criteria space in the form of Interactive Decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…The model specifically targets four objectives: a cost-based objective, an environmental objective concentrating on carbon emission, exhaust emission, wastewater discharge, and solid waste discharge, and two social objectives (i.e., employment and accident rate). Fragoso et al [33] investigated a regional supply chain network in the fishing industry and presented a multi-objective model with six objectives, four of which are economic, one environmental, and one social. Finally, a unique mathematical model for an integrated strategic-tactical SCND problem to quantify the concurrent effects of resilience and sustainability was proposed [129].…”
Section: Mathematical Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The model specifically targets four objectives: a cost-based objective, an environmental objective concentrating on carbon emission, exhaust emission, wastewater discharge, and solid waste discharge, and two social objectives (i.e., employment and accident rate). Fragoso et al [33] investigated a regional supply chain network in the fishing industry and presented a multi-objective model with six objectives, four of which are economic, one environmental, and one social. Finally, a unique mathematical model for an integrated strategic-tactical SCND problem to quantify the concurrent effects of resilience and sustainability was proposed [129].…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…Other methods are introduced and used to solve the multi-objective optimization models [12,23,32,33,108,121,128,130,142,143]. Sharefati et al [12] utilized multi-criteria decision approaches to examine the three pillars of sustainability and identify certain indicators related to the social element.…”
Section: (A) Models With a Single Objectivementioning
confidence: 99%
See 2 more Smart Citations
“…The ε-constraint method is used to validate small-scale problems. Fragoso et al ( 2021 ) suggested a multi-objective mixed integer model for a regional fish processing industry SC network. The model and decision-making process was examined using Pareto frontier approximation and visualization.…”
Section: Literature Reviewmentioning
confidence: 99%